2023
DOI: 10.3389/fpsyt.2022.1078894
|View full text |Cite
|
Sign up to set email alerts
|

CpH methylome analysis in human cortical neurons identifies novel gene pathways and drug targets for opioid use disorder

Abstract: IntroductionDNA methylation (DNAm), an epigenetic mechanism, has been associated with opioid use disorder (OUD) in preclinical and human studies. However, most of the studies have focused on DNAm at CpG sites. DNAm at non-CpG sites (mCpHs, where H indicates A, T, or C) has been recently shown to have a role in gene regulation and to be highly abundant in neurons. However, its role in OUD is unknown. This work aims to evaluate mCpHs in the human postmortem orbital frontal cortex (OFC) in the context of OUD.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Another limitation is that all samples are male, limiting to identify the effect of sex in our results. The analyses were only carried out on CpGs sites and it would be important to conduct a study on non-CpGs sites, because of the role of 5mC at non-CpGs on neuropsychiatric diseases from our group and others ( Jang et al, 2017 ; Nagamatsu et al, 2022 ). Further, since the technologies to assess 5mC and 5hmC in our study and Clark et al, 2022 are different, we were only able to evaluate the convergence between the two studies at the gene-level, not at the CpG level, which limits the interpretation in gene regulatory processes of the differential epigenetic marks identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation is that all samples are male, limiting to identify the effect of sex in our results. The analyses were only carried out on CpGs sites and it would be important to conduct a study on non-CpGs sites, because of the role of 5mC at non-CpGs on neuropsychiatric diseases from our group and others ( Jang et al, 2017 ; Nagamatsu et al, 2022 ). Further, since the technologies to assess 5mC and 5hmC in our study and Clark et al, 2022 are different, we were only able to evaluate the convergence between the two studies at the gene-level, not at the CpG level, which limits the interpretation in gene regulatory processes of the differential epigenetic marks identified.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal nuclei isolation was performed using fluorescence-activated nuclei sorting (FANS), described by Rompala and Nagamatsu et al (2022) ( Rompala et al, 2022 ), obtaining 0.5–1 M NeuN + nuclei for DNA extraction. Sorted nuclei were centrifuged at 1,500 × g for 15 min at 4°C to obtain a pellet.…”
Section: Methodsmentioning
confidence: 99%
“…Efforts to develop new treatment strategies and to bolster avenues of existing treatments for opioid addiction require a deeper understanding of the changes that occur in the human brain with chronic opioid use. To date, few studies have investigated the cellular and molecular changes in the human brain associated with OUD [2][3][4][5][6][7] . Recently, we reported alterations in neuroinflammation, among other pathways, in postmortem brain regions from subjects with OUD 2,5 .…”
Section: Mainmentioning
confidence: 99%
“…Understanding the impact of long-term opioid use and overdose on the human brain is critical for developing new interventions, therapeutics, and for evaluating current OUD treatments. In-depth investigations into the cellular and molecular changes in human postmortem brain may provide valuable insights into the biological mechanisms associated with OUD and lead to new therapeutic strategies for treating opioid addiction [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The dorsolateral prefrontal cortex (DLPFC) and nucleus accumbens (NAc) are key brain regions involved in cognitive, mood, and reward alterations in OUD [9][10][11]. Recent human postmortem brain studies from us [2,3] and others [4,6,12,13] reported a potential interplay between proinflammatory and synaptic remodeling in DLPFC and NAc in OUD. Moreover, we recently implicated circadian rhythm regulation of neuroinflammatory, neurovascular, and neurotransmission (e.g., dopaminergic, GABAergic, and opioidergic signaling) in DLPFC and NAc of OUD subjects [2,3].…”
Section: Introductionmentioning
confidence: 99%